2017
DOI: 10.4236/ojogas.2017.24020
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Effect on the Distribution of Regular Sterane and Geological Significance

Abstract: In order to study thermal effect on distribution characteristics of regular sterane in humic coals, a suit of 25 coals derived from Kuqa Depression in Tarim Basin and Ordos Basin are studied to investigate the distribution of regular sterane in different maturity, which mainly discusses the thermal effect. The results show that the C 27 ααα/C 29 ααα regular sterane ratio has a linear relationship with R o (t max ) and aromatic hydrocarbon maturity parameters in the coals from mature to high-mature stage. It su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…C 27 , C 28 and C 29 steranes were first identified in the American green river and Pre-Cambrian shale by Burlingame (1965) [1]. Then, Eglinton and Calvin (1966) [2] and Eglinton and Murphy (1969) [3] further confirmed the existence of cholestane, ergostane and sitostane.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…C 27 , C 28 and C 29 steranes were first identified in the American green river and Pre-Cambrian shale by Burlingame (1965) [1]. Then, Eglinton and Calvin (1966) [2] and Eglinton and Murphy (1969) [3] further confirmed the existence of cholestane, ergostane and sitostane.…”
mentioning
confidence: 93%
“…Kimble et al (1974) [4] carried out a systematic research on the stereoconfiguration of steranes, and then gave their schematic diagrams and typical mass spectra, laying the foundation for the steroid geochemical attribute research. Based on the study of relative abundance and composition of C 27 , C 28 and C 29 sterols in various organisms and modern sediments in Mexico Bay, Meinshein (1979, 1981) [5] [6] suggested that algae was the predominant primary producer of C 27 -sterols, while C 29 -sterols were more typically associated with terrestrial land plants. On this basis, they proposed the distribution of C 27 , C 28 and C 29 sterols could be used to differentiate the organic matter source.…”
mentioning
confidence: 99%